Review of the current role of targeted therapies as maintenance therapies in first and second line treatment of epithelial ovarian cancer; In the light of completed trials. (February 2016) - Korkmaz, Taner; Seber, Selcuk; Basaran, Gul
Highlights: Targeted therapies in advanced stage ovarian cancer were assessed. Randomized clinical trials were of primary interest of the review. Their effect on survival outcome as well as treatment related adverse events, dose schedules, duration of treatment and magnitude of clinical benefit were discussed in the manuscript. Abstract: Late and recurrent stage ovarian cancer has a high mortality and low response rate to therapy beyond first line treatment. Although first line platinum/taxane based regimens have a satisfactory response rate eventually in most cases disease recurrence is common and second-line treatments are not curative. Delaying progression or recurrence is the main goal of current ongoing clinical studies by means of establishing an effective maintenance regimen with acceptable toxicity profile. Clearly, the persistence of dormant and drug-resistant cells after front-line treatments results in the inability to cure the disease. Over the past several years, the idea of prolongation of therapy for ovarian cancer has garnered clinical attention and academic debate. As a result of a greater understanding of the molecular pathways involved in carcinogenesis and tumor growth, a large number of potential therapeutic targets have been identified and drugs to block receptors, ligands or pathways are being developed. Currently, numerous clinical trials with targeted agents have just been completed or are ongoing involving patients achieving a complete or durable response after first-line and beyond the first line chemotherapy in order to evaluate the efficacy of different therapeutic approaches in terms of progression-free survival and overall survival.